Project-Based Learning Versus Cooperative Learning Courses in Engineering Students - Soto-Gomez, J; Sabattin-Ortega, J; Vargas-Guzman, M; Fuertes-Sanchez, G (IEEE Computer Society, 2015)
This research presents the application of Project-based learning at the School of Engineering of the Catholic University of the North. Three projects were presented to students of different levels of Industrial Engineering and Computer Engineering degree in four undergraduate courses. The innovation in the application of the method is to create transversal work groups to develop multidisciplinary and challenging projects. The planning between courses allowed integrate knowledge, experiences and interests of the various team members. These projects were organized into the following 4 stages; conception, design, implementation and operation. Finally, educational assessment of the impact of Project-based learning methodology was confronted with the method of cooperative learning. The principal advantage of PBL is obtaining better skills and competences developed by students. © 2003-2012 IEEE.